The silver eyes : the graphic novel - Schröder, Claudia; Cawthon, Scott, 1971-; Breed-Wrisley, Kira (Scholastic Inc., 2020)
Contains a graphic novel adaptation of "The Silver Eyes" by Scott Cawthon. It's been ten years since the horrifying murders at Freddy Fazbear's Pizza. Now Charlie and her friends have returned to be part of a scholarship dedication ceremony to the friend they lost that day, but when they return to the abandoned pizzeria, they find out that the horror of that night isn't so far behind them.